The impact of maritime transport financing on total trade in South Africa - Weliswa Matekenya; R. Ncwadi (Journal of Shipping and Trade (JST), 2022)
The study explored the impact of maritime transport financing on trade in South Africa. Using the Autoregressive Distribution lag model, we examine the impact of maritime transport financing on total trade in South Africa during the period 1994 to 2019. The results confirm a long and short-run positive relationship between maritime transport financing and total trade. The findings suggest an overall, substantial investment in maritime transport has the potential to promote trade flows in South Africa. We recommend more investments towards maritime transport infrastructure to ensure a significant increase in exports, and to stimulate economic development in South Africa.
Keywords: F14; H54; L92; 650; ARDL; Financing; Maritime transport; Trade